2016
DOI: 10.1007/s11739-015-1387-1
|View full text |Cite
|
Sign up to set email alerts
|

Mass gathering medicine: event factors predicting patient presentation rates

Abstract: This study was conducted to identify the event characteristics of mass gatherings that predict patient presentation rates held in a southeastern US university community. We conducted a retrospective review of all event-based emergency medical services (EMS) records from mass gathering patient presentations over an approximate 23 month period, from October 24, 2009 to August 27, 2011. All patrons seen by EMS were included. Event characteristics included: crowd size, venue percentage filled seating, venue locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 15 publications
4
39
0
1
Order By: Relevance
“…Understanding crowd behavior in turn allows adequate crowd management assessment in the pre-event phase [43]. In addition, event characteristics, such as the event type, alcohol and drug use, and weather affect the need of medical attention and injury profiles [8,21,[25][26][27][28]42,44]. Our results showed that awareness of event characteristics and the profile of the participants are vital factors to be noted in the emergency plan of a mass gathering event.…”
Section: Factors To Be Noted In the Emergency Planmentioning
confidence: 97%
See 1 more Smart Citation
“…Understanding crowd behavior in turn allows adequate crowd management assessment in the pre-event phase [43]. In addition, event characteristics, such as the event type, alcohol and drug use, and weather affect the need of medical attention and injury profiles [8,21,[25][26][27][28]42,44]. Our results showed that awareness of event characteristics and the profile of the participants are vital factors to be noted in the emergency plan of a mass gathering event.…”
Section: Factors To Be Noted In the Emergency Planmentioning
confidence: 97%
“…Different factors were shown to have an impact on the need of transport to hospital, the number of patients, and the injury patterns. These include weather [13,14], the level of the on-site medical care [15][16][17][18][19][20][21][22][23], audience profile [24], event type [25][26][27], duration [28], and geographical location [29]. Alcohol and drug use, attendance, and the age and mood of the crowd can also have an effect on the level and the need of medical response [28].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, environmental risks threatening the health of participants in MGs included weather risks such as cold, environmental heat,[1215161718192021222324252627282930313233343536373839404142] precipitation,[12] higher humidity,[121520313842] long distance of gatherings and austere environment,[18] mobility of population,[3142] gatherings in outside (external) and unbounded venues,[32] MGs exposed to traffic accidents,[19] the participants’ number and crowd density,[15182028293139] insect bites, and sunburns. [40]…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the risks due to lack of support on resources and inefficiency of gatherings’ safety recognized in this domain were reported as Lack or shortage of patient care workers such as Physicians or Paramedics;[181926313336] flow directions;[20] risk assessment;[20] communication;[20] pre-event advice;[23] a plan for vaccination before gatherings;[2526] coordination;[26] free water as well as terrorist attacks; difficult access to water and food;[28] difficult access to medical facilities;[262732] and duration of MG.[38]…”
Section: Discussionmentioning
confidence: 99%
“…International sporting events like the Olympic Games or the FIFA world cups typically take place outdoors with partially extreme weather conditions. They are attended by people from a wide range of different nations in a rivaling mood or shared identity in regards to the sport match, and a potentially increased use of alcohol and other drugs [10,11].…”
Section: Introductionmentioning
confidence: 99%